Performance Analysis of Wet Gas Flow in Up and Down Transmission Pipelines - Herjuna, Silvester Adi Surya; Labriet, Andrieu; Akbar, Bima; Dimara, Johannes; Kaisiepo, Frans (Institute of Computer Science (IOCS), 2024)
This research examines the performance of wet gas flow in up and down transmission pipelines, addressing the critical challenges and dynamics associated with fluid behavior in varying orientations. Through extensive empirical analysis and modeling, the study identifies key factors influencing slugging, liquid accumulation, and flow efficiency. Findings reveal that upward transmission systems are particularly prone to slugging, leading to operational instability and increased energy demands, while downward flow systems benefit from gravitational assistance, resulting in enhanced reliability and reduced maintenance needs. Additionally, effective liquid management strategies and advanced monitoring technologies are essential for mitigating adverse effects and optimizing system performance. The research also addresses gaps in existing literature by providing new insights into flow management and environmental considerations, offering practical recommendations for pipeline design and operation. Ultimately, this study underscores the importance of ongoing research to refine understanding and improve practices in the transport of wet gas, contributing to the development of sustainable energy solutions.